Estimating the efficiency and potential of China's steel products export to countries along the "Belt and Road" under interconnection: An application of extended stochastic frontier gravity model. (March 2022) - Xu, Jiayue; Lu, Caiwu; Ruan, Shunling; Xiong, Neal N.
Abstract: This study measures the export efficiency and potential of China's steel products to countries along the "Belt and Road" and comprehensively explores the impact of five dimensions of "interconnection" on export efficiency. Thus, we constructed an extended stochastic frontier gravity model (SFGM) based on the yearly data of steel product trade, per-capita gross domestic product (GDP), and common language between China and 54 countries along the "Belt and Road" during 2003–2018. Meanwhile, using quantitative data on multiple indicator levels in the five dimensions of "interconnection", "one-step method" trade inefficiency model was constructed to quantitatively evaluate the impact of "interconnection" on export efficiency and potential. The extended SFGM can make up for the traditional gravity model's overlook of the subjective trade resistance factors that are challenging to quantify, and the "one-step method" trade inefficiency model can avoid the error of the "two-step method" measurement results. The empirical results showed that in the extended SFGM, the positive impact of China's per-capita GDP on export efficiency was stronger than other variables, such as the GDP of countries along the route and common language. The inhibitory effect of China's GDP on export efficiency was more significant than other variables, such as the per-capita GDP of countries along the route and geographical distance. In the trade inefficiency model, free trade agreement(FTA), which represented the degree of policy coordination, played the most significant role in promoting export efficiency. Institutional distance posed a significant obstacle to trade efficiency, while the impact of cultural distance was not significant. Hence, this study discusses corresponding policy recommendations to provide useful ideas for further expanding the potential of steel products trade between China and other countries along the "Belt and Road." Highlights: Develop an extended SFGM for estimating the export efficiency of steel products. A trade inefficiency model is constructed to explore the impact of interconnection on trade efficiency. Compared with other variables, FTAs have the most significant effect on export efficiency. China's export efficiency of steel products to Asia Oceania and South Asia is higher than that of other regions.